VD_FINDINFO HC / 2012 / 762 vom 7. Dezember 2012 - VD Tribunal cantonal (2012)
ACTE DE NON-CONCILIATION, ACCEPTATION TACITE DE COMPÉTENCE, VALEUR LITIGIEUSE, ABUS DE DROIT | 206 al. 2 CPC (CH), 209 CPC (CH), 59 al. 1 CPC (CH), 59 al. 2 CPC (CH), 59 CPC (CH)